Conventional and Microwave Synthesis of 2‐Fluoro‐diazaborolidines and Their Reaction with Lithium Phosphanides. Issue 38 (31st July 2017) - Kaaz, Manuel; Bäucker, Christian; Deimling, Max; König, Simon; Schlindwein, Simon H.; Bender, Johannes; Nieger, Martin; Gudat, Dietrich
Abstract : Condensation of N, N′ ‐disubstituted ethylenediamines with BF3 · OEt2, in the presence or absence of an auxiliary base, gives mixtures of 2‐fluoro‐1, 3, 2‐diazaborolidines and ammonium tetrafluoroborates, respectively. Using BF3 · NEt3 as the reactant allows the introduction of the boron source and the auxiliary in a single component, but suffers from the inhibition of the cyclisation by an excess of free amine formed as a by‐product. In contrast, rapid and quantitative consumption of the starting materials is observed when the reaction is carried out with a 2:1 mixture of BF3 · NEt3 and BF3 · OEt2 per mol of ethylenediamine at elevated temperature. Extremely short reaction times are achieved by conducting the reaction in a superheated solution in a microwave reactor. The 2‐fluoro‐1, 3, 2‐diazaborolidines formed under these conditions are readily isolated in high yields, and their synthetic usability is demonstrated by reactions with lithium phosphanides to give 2‐phosphanyl‐1, 3, 2‐diazaborolidines. Both the F‐ and R2 P‐substituted N‐heterocyclic boranes are fully characterised. In addition, the structural characterisation of an unprecedented BF3 complex of Hünig's base ( i Pr2 EtN) and of a 1, 3, 2‐diazaborolidine–BF3 complex is reported. Abstract : 2‐Fluoro‐1, 3, 2‐diazaborolidines are prepared in one step from amines and BF3 · OEt2 /BF3 · NEt3 by conventional and microwave‐assisted syntheses, and their synthetic use is illustrated by their conversion into 2‐phosphanyl‐diazaborolidines.